PERILAKU PENCEGAHAN KANKER SERVIKS PADA WUS: APAKAH ASPEK KOGNITIF MEMILIKI PENGARUH? - Yulita, Hendra; Rahakbauw, Grenny Zovianny; Dahmar, Dahmar; Dewi, Siti Utami (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Cervical cancer is one of the types of malignant tumors that develop in the cervix or uterine opening. This disease is quite dangerous because in its early stages, it often does not show clear clinical symptoms. The purpose of this study was to determine the relationship between knowledge and cervical cancer prevention behavior in women of childbearing age. The research design used in this study was cross-sectional. The study was conducted in Candi Mulyo Village in September 2024. The population for this study was all women of reproductive age (WUS) in Candi Mulyo Village, totaling 48 individuals. The sample size was 35 respondents. The sampling technique used was accidental sampling. The research instrument used a research questionnaire. Data analysis was conducted using univariate and bivariate methods. The results of the study showed a significant relationship between the level of knowledge (p-value: 0.03) and cervical cancer prevention behavior among women of reproductive age. It is recommended that healthcare workers be more active in providing education about cervical cancer, including its symptoms, causes, and the importance of early detection, as well as expanding the scope of screening services and involving health cadres to reach groups of women of reproductive age who have difficulty accessing healthcare facilities. This will help increase knowledge about cervical cancer through regular health education and check-ups, as well as raise awareness of the importance of early detection of cervical cancer.Keywords: Cancer, Knowledge, Women of Childbearing Age.